Microarray Analysis of the Escherichia Coli Response to Cdte-Gsh Quantum Dots: Understanding the Bacterial Toxicity of Semiconductor Nanoparticles - Vasquez-Guzman, C; Molina-Quiroz, R (BioMed Central Ltd., 2014)
Background: Most semiconductor nanoparticles used in biomedical applications are made of heavy metals and involve synthetic methods that require organic solvents and high temperatures. This issue makes the development of water-soluble nanoparticles with lower toxicity a major topic of interest. In a previous work our group described a biomimetic method for the aqueous synthesis of CdTe-GSH Quantum Dots (QDs) using biomolecules present in cells as reducing and stabilizing agents. This protocol produces nanoparticles with good fluorescent properties and less toxicity than those synthesized by regular chemical methods. Nevertheless, biomimetic CdTe-GSH nanoparticles still display some toxicity, so it is important to know in detail the effects of these semiconductor nanoparticles on cells, their levels of toxicity and the strategies that cells develop to overcome it. Results: In this work, the response of E. coli exposed to different sized-CdTe-GSH QDs synthesized by a biomimetic protocol was evaluated through transcriptomic, biochemical, microbiological and genetic approaches. It was determined that: i) red QDs (5 nm) display higher toxicity than green (3 nm), ii) QDs mainly induce expression of genes involved with Cd+2 stress (zntA and znuA) and tellurium does not contribute significantly to QDs-mediated toxicity since cells incorporate low levels of Te, iii) red QDs also induce genes related to oxidative stress response and membrane proteins, iv) Cd2+ release is higher in red QDs, and v) QDs render the cells more sensitive to polymyxin B. Conclusion: Based on the results obtained in this work, a general model of CdTe-GSH QDs toxicity in E. coli is proposed. Results indicate that bacterial toxicity of QDs is mainly associated with cadmium release, oxidative stress and loss of membrane integrity. The higher toxicity of red QDs is most probably due to higher cadmium content and release from the nanoparticle as compared to green QDs. Moreover, QDs-treated cells become more sensitive to polymyxin B making these biomimetic QDs candidates for adjuvant therapies against bacterial infections. © 2014 Monrás et al.
Keywords: Toxicity mechanism; Transcriptomic response; Oxidative stress; Cadmium; Nanoparticles